Hydroethanolic extracts from Bauhinia guianensis: a study on acute toxicity in Zebrafish embryos and adults - Rosemary de Carvalho Rocha Koga; Gisele Custodio de Souza; Abrahão Victor Tavares de Lima Teixeira; Adriana Maciel Ferreira; Brenda Lorena Sánchez-Ortiz; Lucas Silva Abreu; Josean Fechine Tavares; José Carlos Tavares Carvalho (Taylor & Francis Group, 2024)
Context The botanical species Bauhinia guianensis Aublet (Leguminosae-Cercidoideae) is traditionally used in the Amazon for medicinal purposes.Objective The acute toxicity of the hydroethanolic extracts from B. guianensis leaves and stems (HELBg and HESBg) was evaluated in zebrafish (Danio rerio), with emphasis on the embryonic developmental stage and adult alterations.Materials and methods Extracts were analyzed on LC-DAD-MS/MS. Zebrafish eggs were inoculated individually with concentrations of HELBg and HESBg (0.25, 0.5, 0.75, 1.0, and 1.5 µg/mL), observed for 96 h. Adult zebrafish were treated with a single oral dose (100, 200, 500, 1000, and 2000 mg/kg) of HELBg and HESBg, observed for 48 h.Results HELBg and HESBg analysis detected 55 compounds. Both extracts exhibited toxicity, including embryo coagulation at higher doses of HELBg and absence of heartbeats in embryos at all doses of HESBg. Behavioral variations were observed; tissue alterations in adult zebrafish were found at the highest doses, primarily in the liver, intestine, and kidneys because of HELBg and HESBg effects. The LD50 of HESBg was 1717 mg/kg, while HELBg exceeded the limit dose of 2000 mg/kg.Conclusions The study on acute toxicity of B. guianensis extracts exhibits significant toxic potential, emphasizing effects on embryonic and adult zebrafish. The results suggest relative safety of the species preparations, encouraging further clinical trials on potential biological activities.